POTENTIAL COMPLICATIONS OCCURING AS A RESULT OF INCIDENTAL DETECTION OF UNTREATED ASYMPTOMATIC APICAL PERIODONTITIS. REVIEW OF LITERATURE. - Shugaa Nasir Alotaibi, Khalid M Alotaibi, Abdulaziz A Alamro, Sharifah S Alzaidi, Maha M Alotaibi, Nada A Softah, (Chelonian Research Foundation, 2024)
The incidental detection of asymptomatic apical periodontitis prompts the question of whether or not this lesion should be treated. Arguments favoring treatment are that the inflammation may cause pain in the future, may enlarge, or may negatively affect the host's resistance. Reasons for not treating may be that treatment weakens the tooth, may cause iatrogenic damage, and that treatment is expensive and burdensome for the patient and does not lead to complete recovery in all cases. A lack of scientific evidence exists to support either option, whether it involves treating the lesion or not.